Analysis of the game Racing Limits as a teaching instrument of kinematics (Research, Society and Development, 2019)
This article aims to analyze the electronic game Racing Limits, to identify whether there are coerces or inconsistencies in the numerical values related to the quantities displacement, speed and time provided by him and propose the game as a teaching tool of Kinematics. To do so, we apply the scalar velocity equation to assess whether there is equivalence between the speeds provided by the game and the calculated speeds. With our research, it was possible to conclude that there is equivalence between the values of the velocities provided by the game and the calculated speeds, which allowed us to interpret this game as coherent. In this way, we propose that teachers use the game in the classroom, instigating students to do the same analysis of the game.